Study of chromatin remodeling genes implicates SMARCA4 as a putative player in oncogenesis in neuroblastoma. Issue 10 (31st May 2019) - Bellini, Angela; Bessoltane‐Bentahar, Nadia; Bhalshankar, Jaydutt; Clement, Nathalie; Raynal, Virginie; Baulande, Sylvain; Bernard, Virginie; Danzon, Adrien; Chicard, Mathieu; Colmet‐Daage, Léo; Pierron, Gaelle; Le Roux, Laura; et al.
Abstract : In neuroblastoma (NB), genetic alterations in chromatin remodeling (CRGs) and epigenetic modifier genes (EMGs) have been described. We sought to determine their frequency and clinical impact. Whole exome (WES)/whole genome sequencing (WGS) data and targeted sequencing (TSCA®) of exonic regions of 33 CRGs/EMGs were analyzed in tumor samples from 283 NB patients, with constitutional material available for 55 patients. The frequency of CRG/EMG variations in NB cases was then compared to the Genome Aggregation Database (gnomAD). The sequencing revealed SNVs/small InDels or focal CNAs of CRGs/EMGs in 20% (56/283) of all cases, occurring at a somatic level in 4 (7.2%), at a germline level in 12 (22%) cases, whereas for the remaining cases, only tumor material could be analyzed. The most frequently altered genes were ATRX (5%), SMARCA4 (2.5%), MLL3 (2.5%) and ARID1B (2.5%). Double events (SNVs/small InDels/CNAs associated with LOH) were observed in SMARCA4 ( n = 3), ATRX ( n = 1) and PBRM1 ( n = 1). Among the 60 variations, 24 (8.4%) targeted domains of functional importance for chromatin remodeling or highly conserved domains but of unknown function. Variations in SMARCA4 and ATRX occurred more frequently in the NB as compared to the gnomAD control cohort (OR = 4.49, 95%CI: 1.63–9.97, p = 0.038; OR 3.44, 95%CI: 1.46–6.91, p = 0.043, respectively). Cases with CRG/EMG variations showed a poorer overall survival compared to cases without variations. Genetic variations of CRGs/EMGs with likely functional impact were observed in 8.4% (24/283) of NB. Our case–control approach suggests a role of SMARCA4 as a player of NB oncogenesis. Abstract : What's new? Mutations that affect chromatin remodeling can lead to cancer. In this paper, the authors investigated the impact of variations in chromatin remodeling genes and epigenetic modifier genes on neuroblastoma patients. They compared the frequency of these variations in NB cases with data from the Genome Aggregation Database (gnomAD). Neuroblastoma cases had a higher frequency of SMARCA4 and ATRX gene variations than the general population. Furthermore, NB patients with CRG/EMG mutations had poorer overall survival than NB cases without such mutations. These findings highlight the importance of chromatin remodeling in neuroblastoma as an avenue for new therapeutics.